Investigating the Dynamics of a Soft Crystalline Covalent Organic Framework during Benzene and Cyclohexane Adsorption by in situ Powder X‐ray Diffraction - Anna Mauri; Rebecca Vismara; Marco Moroni; Esther Roldán‐Molina; Jorge A. R. Navarro; Simona Galli (Small Science)
Due to their similar boiling points, separation of benzene and cyclohexane mixtures is among the current challenging processes faced by the petrochemical industry. As recently assessed, the soft imine‐based covalent organic framework [(TAM)(BDA)2] (COF‐300; TAM = tetrakis(4‐aminophenyl)methane, BDA = terephthaldehyde) possesses higher affinity for benzene than cyclohexane in both static conditions at 298 K and dynamic conditions in the range of 298–348 K. As shown in this contribution, in situ powder X‐ray diffraction while dosing benzene and cyclohexane vapors in the range of 0.01–4.74 bar on the narrow‐pore form of COF‐300 confirmed the coherent switchability of its framework, unveiling the progressive formation of different intermediate‐ and large‐pore forms. In addition, a basket of otherwise inaccessible key crystallochemical details—“on/off” structural‐feature changes cooperating to adsorption, primary adsorption sites, and host–guest and guest–guest interactions—was successfully retrieved. Overall, these findings allowed to shed light on the framework dynamics underneath the previously observed selectivity toward benzene over cyclohexane, completing this case of study and providing relevant information for the design of new‐generation adsorbents for this applicative context.